The meningeal lymphatics: regulators of Aβ immunotherapy?. Issue 11 (November 2021) - Laaker, Collin; Fabry, Zsuzsanna
Abstract : A new study by Da Mesquita et al . reports on how meningeal lymphatic modulation may influence amyloid-beta immunotherapy and microglial function in mouse models of Alzheimer's disease (AD). This research has broad implications for unraveling the role meningeal lymphatics may play in regulating immunity in the brain during AD pathology and treatment.